Lower cancer incidence three years after COVID-19 infection in a large veteran population - Jerry Bradley; Fei Tang; Natasha M. Resendes; Dominique M. Tosi; Iriana S. Hammel (PLoS ONE, 2025)
Background The role of COVID-19 infection in cancer incidence risk is not known. COVID-19 infection may lead to increased cancer risk, as seen with other viruses, or to decreased risk due to the activation of the immune response during acute infection. This study aimed to determine the association between cancer incidence in US Veterans and COVID-19 infection. Methods We conducted a retrospective cohort study of US Veterans comparing those who tested positive for COVID-19 during the first wave of COVID-19 between March 15, 2020, and Nov 30, 2020, to those who tested negative. We used data from the COVID-19 Shared Data Resource and Cox proportional hazard regression models to determine the hazard ratio of a new cancer diagnosis within a three-year follow-up period for the COVID-19 positive patients compared to those who were negative. Covariates included age, race, ethnicity, sex, BMI, smoking, being an active patient in the VHA system within a year of the COVID-19 test, and other factors. Results 499,396 patients were included in this study, with 88590 (17.2%) COVID-19 positive, 427566 (82.8%) COVID-19 negative. The ages of the COVID-19 positive and negative patients were 57.9 ± 16.4 and 59.5 ± 15.8, respectively. For those who survived for at least 30 days after COVID-19 testing, COVID-19 infection was associated with a 25% reduction in the hazard of cancer (HR = 0.75, 95% CI: 0.73–0.77). The reduction of the hazard was similar across sexes and races, except in Asians. Above 45 years of age, the hazard of cancer incidence further decreased with advancing age. Conclusions Patients who were diagnosed with COVID-19 in the first wave of the pandemic had a decreased risk of cancer incidence in a 3-year follow-up across gender and race. Further multicenter prospective cohort studies are needed to evaluate the mechanism of this interaction.